Sinonasal Disease in Polyostotic Fibrous Dysplasia and McCune-Albright Syndrome - DeKlotz, Timothy R. (2013)
OBJECTIVES: To characterize the spectrum, symptoms, progression and effects of endocrine dysfunction on sinonasal disease in polyostotic fibrous dysplasia (PFD) and McCune-Albright Syndrome (MAS). STUDY DESIGN: Retrospective review. METHODS: A prospectively followed cohort of subjects with PFD/MAS underwent a comprehensive evaluation that included otolaryngologic and endocrine evaluation, and imaging studies. Head and facial CT scans were analyzed, and the degree of fibrous dysplasia (FD) was graded using a modified Lund-MacKay scale. Those followed for more than 4 years were analyzed for progression. RESULTS: A total of 106 patients meeting inclusion criteria were identified with craniofacial FD. A majority (92%) demonstrated sinonasal involvement. There were significant positive correlations between the sinonasal FD scale score and chronic congestion, hyposmia, growth hormone excess and hyperthyroidism (p < 0.05 for all). Significant correlations were not found for headache/facial pain or recurrent/chronic sinusitis. Thirty-one subjects met the criteria for longitudinal analysis (follow-up mean 6.3 years, range 4.4 – 9 years). Those demonstrating disease progression were significantly younger than those who did not (mean age = 11 vs. 25 years). Progression after age of 13 years was uncommon (n=3) and minimal. Concomitant endocrinopathy or bisphosphonate use did not have any significant effect on progression of disease. CONCLUSION: Sinonasal involvement of fibrous dysplasia in PFD/MAS is common. Symptoms are usually few and mild, and disease progression occurs primarily in young subjects. Concomitant endocrinopathy is associated with disease severity, but not progression.